The positive outcome of educating HIV‐infected children about beauty in an African village. Issue 2 (12th January 2021) - Papi, Massimo; Fiscarelli, Ersilia
Abstract: We report the interesting experience of the African Village of Hope (Dodoma, Tanzania) where HIV‐positive orphan children have been hosted, cured, and educated in the last 15 years. The particular attention to beauty in the education of the children amazed us when we were in the village working as doctors. The project and the effort to create such a model of social and medical assistance were born from the idea of the founders, Sister Maria Rosaria Gargiulo and Don Vincenzo Boselli. In light of this experience and of the healthy result obtained in the village, we believe that education in the perception of beauty is a formative aspect for all children, but may also be a powerful adjuvant therapy in severely immunocompromised young patients.